2006
DOI: 10.1128/jcm.00024-06
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time PCR Assay for Detection and Quantification of Hepatitis B Virus Genotypes A to G

Abstract: The detection and quantification of hepatitis B virus (HBV) DNA play an important role in diagnosing and monitoring HBV infection as well as assessing therapeutic response. The great variability among HBV genotypes and the enormous range of clinical HBV DNA levels present challenges for PCR-based amplification techniques. In this study, we describe the development, evaluation, and validation of a novel real-time PCR assay designed to provide accurate quantification of DNA from all eight HBV genotypes in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 34 publications
1
33
0
2
Order By: Relevance
“…Comparison of the two assays for quantitative detection of HBV DNA levels in the 118 serum samples showed that the two sets of results were highly correlated (r = 0.948, P < 0.001). This was in accordance with the results of previous studies that have evaluated other realtime PCR assays for quantitation of HBV DNA [13,14,[22][23][24][25][26] .…”
Section: Discussionsupporting
confidence: 92%
“…Comparison of the two assays for quantitative detection of HBV DNA levels in the 118 serum samples showed that the two sets of results were highly correlated (r = 0.948, P < 0.001). This was in accordance with the results of previous studies that have evaluated other realtime PCR assays for quantitation of HBV DNA [13,14,[22][23][24][25][26] .…”
Section: Discussionsupporting
confidence: 92%
“…Several recent articles compared results of HBV DNA quantification between the Versant branched DNA (bDNA) assay, using hybridization with multiple regions of the genome and presumably detecting both spliced and unspliced DNA (total DNA), and other quantitative assays using primers from the S region (Abbott RealTime HBV DNA and an in-house assay) (24,38) or the Roche Cobas TaqMan HBV DNA quantitative assay assumed to use S primers (detect only unspliced HBV DNA) (2,11,25) and another in-house assay using X region primers detecting both spliced and unspliced total HBV DNA (37). For the Abbott assay, the viral load was overall lower than it was with the bDNA assay but more so in 26% of sample pairs of genotypes C and A but not E (24) and lower by 0.67 log in Taiwanese samples mostly of genotype B (38).…”
Section: Discussionmentioning
confidence: 99%
“…Three different hairpin probes (probe-HBV-1, probe-HBV-2and probe-HBV-3) and corresponding primers were designed against the different conserved regions of the HBV genome including overlapping genes encoding X-protein, S gene and X gene region [2,21,22] (Table S2, S3 & S4). Under the optimized PCR amplification conditions of corresponding probes, the different colorimetric results by using those three pairs of probes were turned out (Fig.…”
Section: Evaluation and Selection Of Different Hbv Probesmentioning
confidence: 99%